Feeding behavior, nutrient digestibility, feedlot performance, carcass traits, and meat characteristics of crossbred lambs fed high levels of yellow grease or soybean oil - Scarpino van Cleef, Flavia de Oliveira [UNESP]; Bertocco Ezequiel, Jane Maria [UNESP]; D'Aurea, Andre Pastori [UNESP]; Costa Almeida, Marco Tulio [UNESP]; Perez, Henrique Leal [UNESP]; Castello Branco van Cleef, Eric Haydt [UNESP] (Elsevier B.V., 2016)
Twenty-four crossbred (Santa Ines x Dorper) non-castrated male lambs (initial body weigh 24.9 kg +/- 2.4 kg), were used to evaluate the effects of lipid sources (soybean oil or frying soybean oil) on feeding behavior, feedlot performance, digestibility of dry matter and nutrients of finishing lamb diets. The animals were distributed in a randomized block design and assigned to one of the isonitrogenous (18.4% CP, DM basis) diets which were formulated in forage:concentrate ratio of 40:60. The control treatment (CTL) was composed of corn silage, corn grain, sunflower meal, soybean hulls, urea, limestone and minerals. The other two treatments contained 6% soybean oil (SO) or 6% residual soybean frying oil (YG) on DM basis, mainly replacing corn grain and soybean hulls. Animals were offered total mixed rations twice daily ad libitum. Animals were harvested at 35 kg BW, and carcass characteristics data were recorded. Samples of Longissimus muscle were collected for centesimal composition analysis. The feeding behavior was observed for 3 consecutive days (12 h period each). The apparent digestibility of DM and nutrients of experimental diets were estimated using the internal marker indigestible acid detergent fiber. The oil supplementation, regardless of the source, did not change feeding behavior and carcass characteristics. Dry matter and nutrient intake and digestibility were decreased when animals were fed oil, except for ether extract, which increased. Animals fed YG presented lesser average daily weight gain (177.7 g) than SO-fed lambs (205.3 g). In conclusion, the addition of soybean oil or yellow grease at 6% in diet DM for feedlot crossbred lambs has minimal effects on feeding behavior and increases feed efficiency, however decreases digestibility of DM, NDF and ADF, and tends to increase intramuscular fat. The use of yellow grease as an alternative energy source increases lambs' days on feed. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: By-products; Digestion; Frying oil; Performance; Sheep; Soybean oil